Magneto-Optical Analysis of Magnetic Anisotropy in Ultrathin Tm$_{3}$Fe$_{5}$O$_{12}$/Pt Bilayers - Nunley, T. Nathan; Russell, Daniel; Chang, Liang-Juan; Lujan, David; Choe, Jeongheon; Guo, Side; Lee, Shang-Fan; Yang, Fengyuan; Li, Xiaoqin (2025)
Magnetic bilayers consisting of an epitaxially grown ferrimagnetic insulator and a heavy metal layer are attractive for spintronic application because of the opportunity for electric control and read-out of spin textures via spin orbit torque. Here, we investigate ultrathin thulium iron garnet (TmIG)/Pt bilayers when the TmIG layer thickness is 3 nm and below using a sensitive Sagnac magneto-optical Kerr effect technique. We compare the hysteresis loops from out-of-plane and in-plane applied magnetic fields. The preferred magnetization orientation evolves with the TmIG thickness and the presence of the Pt overlayer. We quantify the evolution of the magnetic anisotropy in these ultrathin films and find a significant change even when the TmIG thickness is varied by less than 1 nm. In these ultrathin films, the presence of a Pt overlayer changes the effective anisotropy field by more than a factor of 2, suggesting that the interfacial anisotropy at the Pt/TmIG interface plays a critical role in this regime.